2016
DOI: 10.1016/j.jelekin.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Surface electromyography in animal biomechanics: A systematic review

Abstract: The study of muscle activity using surface electromyography (sEMG) is commonly used for investigations of the neuromuscular system in man. Although sEMG has faced methodological challenges, considerable technical advances have been made in the last few decades. Similarly, the field of animal biomechanics, including sEMG, has grown despite being confronted with often complex experimental conditions. In human sEMG research, standardised protocols have been developed, however these are lacking in animal sEMG. Bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 94 publications
1
35
0
Order By: Relevance
“…Similar questions arise for SP practices involving sEMG signal normalisation. Valentin and Zsoldos (2016) reported that normalisation techniques are frequently absent in the equine sEMG literature, but no studies have demonstrated the consequences of this on the interpretation of equine sEMG data. In the human literature, Lehman and McGill (1999) investigated the effect of normalisation on the sensitivity of sEMG outcome measures for analysing the relationship between upper and lower rectus abdominus (RA) during a trunk curl exercise.…”
Section: The Removal Of Low-frequency Noise Contamination Within Semgmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar questions arise for SP practices involving sEMG signal normalisation. Valentin and Zsoldos (2016) reported that normalisation techniques are frequently absent in the equine sEMG literature, but no studies have demonstrated the consequences of this on the interpretation of equine sEMG data. In the human literature, Lehman and McGill (1999) investigated the effect of normalisation on the sensitivity of sEMG outcome measures for analysing the relationship between upper and lower rectus abdominus (RA) during a trunk curl exercise.…”
Section: The Removal Of Low-frequency Noise Contamination Within Semgmentioning
confidence: 99%
“…Unfortunately, standards for sEMG signal detection and processing in equine subjects are not currently available and methodological variation within equine sEMG literature is particularly evident for SP methods (Valentin and Zsoldos, 2016). Furthermore, fundamental lowfrequency noise attenuation and normalisation techniques are absent, or not consistently applied in the equine sEMG literature (Valentin and Zsoldos, 2016). Reliance on human subject-based sEMG guidelines for equine subjects is not recommended, as differences in size, mass, bipedal vs. quadrupedal gait and skin properties alone are sufficient to question their equivalence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that ENMG plays role in detecting the muscle activity in the patients with chronic respiratory disease [2], evaluating the respiration pattern of newborn baby, predicting the lung function of the children with asthma [3], detecting speaking ability in deaf people [4], and fatigue analysis [5]. The ENMG is not only a powerful tool for study the muscle function in human, but also in animals [6].…”
Section: Introductionmentioning
confidence: 99%
“…Of all animals, horses have most commonly been investigated using sEMG in a large number of studies (cf Valentin and Zsoldos [ 13 ]). This is due to the importance of their musculoskeletal system for their use, but also due to the large superficial muscle areas available for sEMG such as leg and back muscles.…”
Section: Introductionmentioning
confidence: 99%